2009
DOI: 10.1007/s12194-009-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of pulmonary blood flow evaluation method with a dynamic flat-panel detector: quantitative correlation analysis with findings on perfusion scan

Abstract: Pulmonary blood flow is reflected in dynamic chest radiographs as changes in X-ray translucency, i.e., pixel values. Thus, decreased blood flow should be observed as a reduction of the variation of X-ray translucency. We performed the present study to investigate the feasibility of pulmonary blood flow evaluation with a dynamic flat-panel detector (FPD). Sequential chest radiographs of 14 subjects were obtained with a dynamic FPD system. The changes in pixel value in each local area were measured and mapped on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Digital dynamic radiography is a completely novel modality that can capture images similar to those of pulmonary angiography and scintigraphy 8,11,12,15,16 in a short time. Moreover, it does not require the use of contrast media.…”
Section: F I G 4 Pulmonary Perfusion Images and Respiratory Artifamentioning
confidence: 99%
See 4 more Smart Citations
“…Digital dynamic radiography is a completely novel modality that can capture images similar to those of pulmonary angiography and scintigraphy 8,11,12,15,16 in a short time. Moreover, it does not require the use of contrast media.…”
Section: F I G 4 Pulmonary Perfusion Images and Respiratory Artifamentioning
confidence: 99%
“…In addition to the protocol, there are two other differences between the present study and previous studies. 11,12,15,16 The first is that the present study included the largest number of patients examined in this field. Thus far, only a few number of case reports, preliminary studies, and animal experiments 14 have been reported on DDR technology for pulmonary perfusion.…”
Section: F I G 4 Pulmonary Perfusion Images and Respiratory Artifamentioning
confidence: 99%
See 3 more Smart Citations